Isolated Unilateral Vocal Fold Palsy following Skull Base Fracture: A Case Report - MB, Marina; NM, Hazleigh; YK, Thean; A., Sani (IIUM Medical Journal Malaysia, 2018)
Isolated lower cranial nerve (CN) palsy affecting the CN X resulting from a skull base fracture is very rare. The clinical manifestation and natural history is related closely to the complex anatomy of this region and mechanism of injury. Here, we report a case of a 54 year-old man who presented with a delayed onset of dysphonia and dysphagia with aspiration following a closed head injury sustained from a motor vehicle accident. Injection laryngoplasty was implemented to alleviate symptoms of his CN X palsy, which eventually almost completely resolved. High index of suspicion should be maintained when investigating possible skull base fractures, especially with a suggestive clinical presentation of lower CN palsies affecting one or all the lower CNs. Delayed onset of these CN palsies are likely to have more favourable outcomes.